Modulation of Giant Magnetoimpedance Effect in Co-Based Amorphous Wires by Carbon-Based Nanocoatings - Zhen Yang; Jiabao Huang; Jingyuan Chen; Chong Lei (C)
Co-based amorphous wires (Co-AWs) are functional materials renowned for their high impedance change rate in magnetic fields and a pronounced giant magnetoimpedance (GMI) effect. In this study, magnetron sputtering (MS) and dip-coating (DC) techniques were employed to fabricate carbon-based nanocoatings aimed at modulating the GMI properties of Co-AWs. The magnetic properties and GMI responses of the composite Co-AWs with carbon-based coatings were comparatively analyzed. The results demonstrate that both methods effectively enhanced the GMI properties of the coated Co-AWs. The DC method emerged as a rapid and efficient approach for forming the coated film, achieving a modest enhancement in GMI performance (10% enhancement). In contrast, the MS technique proved more effective in improving the GMI effect, yielding superior results. Co-AWs coated via Ms exhibited smoother surfaces and reduced coercivity. Notably, the GMI effect increased with the thickness of the sputtered carbon coatings, reaching a maximum GMI effect of 522% (a remarkable 357% enhancement) and a sensitivity of 33.8%/Oe at a coating thickness of 334 nm. The observed trend in the GMI effect with carbon layer thickness corresponded closely to variations in transverse permeability, as determined by vibrating sample magnetometry (VSM). Furthermore, the carbon coating induced changes in the initial quenching stress on the surface of the Co-AWs, leading to alterations in impedance and a significant reduction in the characteristic frequency of the Co-AWs. Our findings provide valuable insights into the modulation of GMI properties in Co-AWs, paving the way for their optimized application in advanced magnetic sensor technologies.